An exploratory analysis of low-ozone events during spring and summer months over Cape Point, South Africa - (:unkn) unknown (My University, 2018)
Decreased stratospheric ozone levels contribute towards increased ultraviolet (UV) radiation at the Earth's surface with potential negative impacts on public health. This study sought to determine whether or not the break-up of the polar vortex has an effect on stratospheric ozone levels and the resulting UV-B radiation at Cape Point. Using a dynamical model, it was shown that the polar vortex has a limited effect on ozone levels at Cape Point in September and that tropical air-masses had a larger impact on ozone levels during summer months. Decreased levels of stratospheric ozone resulted in increased UV radiation at the surface.
Keywords: African Research